2015
DOI: 10.1007/s10597-015-9889-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender Explain the Relationship Between Occupation and Suicide? Findings from a Meta-Analytic Study

Abstract: This report investigated whether suicide risk by occupational groups differed for males and females. We examined this using a sub-set of articles examined in a recent meta-analysis and stratified by gender. For certain occupational groups, males and females had a similar risk of suicide (the military, community service occupations, managers, and clerical workers). There was some indication of gender differences for other occupations (technicians, plant and machine operators and ship's deck crew, craft and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
1
6
0
2
Order By: Relevance
“…This finding extends previous research, which has suggested males -more than females -are particularly vulnerable to problems related to the inability to effectively fulfil the "breadwinner" role traditionally considered as central to hegemonic masculinity [38]. Past research has also indicated that males appear to have substantially elevated suicide rates in low-skill jobs that have traditionally been characterised as having poor psychosocial job quality [29,39,40].…”
Section: Discussionsupporting
confidence: 81%
“…This finding extends previous research, which has suggested males -more than females -are particularly vulnerable to problems related to the inability to effectively fulfil the "breadwinner" role traditionally considered as central to hegemonic masculinity [38]. Past research has also indicated that males appear to have substantially elevated suicide rates in low-skill jobs that have traditionally been characterised as having poor psychosocial job quality [29,39,40].…”
Section: Discussionsupporting
confidence: 81%
“…In recent years, the phenomenon of suicide in the workplace has increased gradually (Mohseni-Cheraghlou, 2013). Numerous studies have found that certain occupations are at elevated risk of suicide compared with the general population, and females display a higher risk of suicide than males among the working population (Milner et al, 2016). Discrimination against global women significantly correlated with the prevalence of suicide among females and the high suicide ratio of females compared to males in Asia may in part be due to problems related specifically to family preferences for sons over daughters as revealed by the much higher intra-household investments in caring for, nurturing, and allocating resources to sons relative to daughters (Kwak et al, 2016; Pugh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the gender occupational risk of suicide, Greek women between the ages of 50 to 59 seem to have an increase in their risk during the austerity years of 2010 and 2012. Considering the need of research on the occupational risk of suicide between sexes, further studies should investigate whether the extent of the recent economic crisis differentiated the risk of suicide between employed females and males [25].…”
Section: Discussionmentioning
confidence: 99%